IMPACT OF PETROCHEMICAL ACTIVITIES ON THE PHYSICOCHEMICAL AND MICROBIOLOGICAL QUALITY OF SURFACE WATER, GROUND WATER AND SOIL IN OTU-JEREMI, IWEREHKAN AND OKPARE COMMUNITIES, UGHELLI SOUTH LOCAL GOVERNMENT AREA, DELTA STATE, NIGERIA - Omoruyi, Iyekhoetin Matthew; Amadi, James Ikechukwu (FUDMA JOURNAL OF SCIENCES, 2022)
The effects of petrochemical activities on the physicochemical and microbiological properties of surface water, ground water and soil from three different communities (Otu-Jeremi, Iwerehkan and Okpare communities) in Ughelli South Local Government Area, Delta State, Nigeria was investigated. A total of 96 samples, were obtained from surface water, ground water as well as soil, and across two seasons (dry and raining). The physicochemical parameters were determined according to the American Public Health Association (APHA) methods, while total heterotrophic bacterial counts and fungal counts were determined by pour plate technique. The results obtained showed that most pH obtained from underground water, surface water and soil were below the acceptable limit, including that of the control. The turbidity level of the surface water samples from all communities (Otu-Jeremi, 4.01 ± 0.3 NTU; Iwerehkan, 3.28 ± 0.89 NTU; Okpare, 3.25 ± 0.89 NTU), including that of the control (3.65 NTU) during the dry season were higher than that of Federal Environmental Protection Agency (FEPA) benchmark (1.0 NTU). Other parameters had varying concentrations, when compared with the FEPA minimum benchmark. Six bacterial genera (Aeromonas sp, Corynebacterium sp, Staphylococcus sp, Micrococcus sp, Bacillus sp and Pseudomonas sp.) and seven fungi genera (Aspergillus, Cladosporium, Candida, Mucor, Rhizopus, Trichophyton and Geotrichium) were identified. The result of this study showed that petrochemical activities have negative impact on underground water, surface water and soil from the three communities in Ughelli South Local Government Area of Delta State